MENGELOLA KELELAHAN/ FATIQUE MANAGEMENT CASE KECELAKAAN TRANSPORTASI DAMPAK DARI KELELAHAN PENGENDARA KENDARAAN - Suryatno Marmo; Erna Indriastiningsih; Anita Oktavia Trisna Devi (JURNAL GAUNG INFORMATIKA, 2016)
The development of transportation facilities has become increasingly rapid and complex so that it becomes a problem as time goes on. In order to make effective,efficient and productive human mobility capital transportation facilities in a steady balance between comfort and human mobility that is effective, efficient and productive,in its use there tends to be deviations from users of transportation capital. From year to year, accident data is increasing so that the Government is responsible for ensuringtraffic safety and road transportation. Where the purpose of this study is to identify the main causes of traffic accidents and provide advice to drivers to prevent / reduce trafficaccidents. The government has provided various regulations regarding traffic that must be obeyed. The regulation is one of them is how to drive well and safely (driving in prime body condition), the impact caused by physical fatigue / physical factors (body that is not prime) is so great with the traffic accident data above. So it is very important to manage the body to stay fit while driving. If studied in terms of productivity and efficiency, it also has a significant impact if people work / act in physical / physical fatigue conditions.